Women's Fertility Status Alters Other Women's Jealousy and Mate Guarding. (February 2017) - Hurst, Ashalee C.; Alquist, Jessica L.; Puts, David A.
Across three studies, we tested the hypothesis that women exhibit greater jealousy and mate guarding toward women who are in the high (vs. low) fertility phase of their cycle. Women who imagined their partner with a woman pictured at high fertility reported more jealousy than women who imagined their partner with a woman pictured at low fertility (Studies 1 and 2). A meta-analysis across studies manipulating fertility status of the pictured woman found a significant effect of fertility status on both jealousy and mate guarding. Women with attractive partners viewed fertile-phase women as less trustworthy, which led to increased mate guarding (Study 2). In Study 3, the closer women were to peak fertility, the more instances they reported of other women acting jealously and mate guarding toward them. These studies provide evidence that women selectively exhibit jealousy and mate guarding toward women who are near peak fertility.